1993
DOI: 10.1128/mcb.13.3.1847
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Ke 6, a novel gene encoded within the major histocompatibility complex, in murine polycystic kidney disease.

Abstract: Polycystic kidney disease (PKD) is characterized by progressive enlargement of the kidneys due to numerous expanding cysts ultimately leading to renal failure. We have identified a gene, Ke 6, located within the H-2K/tw5 region on mouse chromosome 17, which is downregulated in two distinct murine models of heritable PKD. Ke 6 is a member of the short-chain alcohol dehydrogenase family and possess remarkable amino acid sequence conservation with several bacterial proteins with oxidoreductase function. The Ke 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…This area is well known to contain genes encoding the human major histocompatibility complex (MHC). This complex is thought to be involved in polycystic kidney disease (PKD) since aberrant expression has been found in two different models of PKD mice (Aziz et al 1993). Recently, Fomitcheva et al (1998) have found that the overexpressed protein fused with GST catalyzes efficiently the transformation of E 2 to E 1 .…”
Section: Type 8 17 -Hsdmentioning
confidence: 99%
“…This area is well known to contain genes encoding the human major histocompatibility complex (MHC). This complex is thought to be involved in polycystic kidney disease (PKD) since aberrant expression has been found in two different models of PKD mice (Aziz et al 1993). Recently, Fomitcheva et al (1998) have found that the overexpressed protein fused with GST catalyzes efficiently the transformation of E 2 to E 1 .…”
Section: Type 8 17 -Hsdmentioning
confidence: 99%
“…For example, germline mutations in 173-HSD 3 and 4 result in the male pseudohermaphroditism (Geissler et al, 1994) and the fatal form of Zellweger syndrome (de Launoit and Adamski, 1999; Peltoketo et al, 1999), respectively. Abnormal regulation of 17p-HSD8 {Ke 6), an alternatively spliced gene member of the SDR family, has been linked to recessive polycystic kidney disease in mice (Aziz et al, 1993). Allelic variants in the 3p-HSD 2 gene, encoding one of two enzymes that initiates the inactivation of dihydrotestosterone, have been identified and are currently under assessment for a role in racial/ethnic differences in prostate carcinogenesis (Devgan et al, 1997).…”
Section: Mapping Ofpsdrl To Chromosome 12mentioning
confidence: 99%
“…We reported the identification of a new mammalian gene, Ke 6, whose expression is specifically repressed in two different murine models of PKD: the cpk and jck mouse (7). The Ke 6 gene is encoded within the major histocompatibility complex and is a member of the superfamily of short-chain alcohol dehydrogenases.…”
Section: Polycystic Kidney Disease (Pkd)mentioning
confidence: 99%
“…The Ke 6 gene is encoded within the major histocompatibility complex and is a member of the superfamily of short-chain alcohol dehydrogenases. The normal expression pattern of the Ke 6 gene is very high in kidney and liver (7), the two organs that are most extensively affected in polycystic kidney disease. We have postulated that the Ke 6 gene may encode steroid dehydrogenase activity, since it has substantial homology to specific functional domains of bacterial and mammalian steroid dehydrogenases (8).…”
Section: Polycystic Kidney Disease (Pkd)mentioning
confidence: 99%